PERANCANGAN APLIKASI ANDROID PARIWISATA RAUN MINANGKABAU - MONICA PRIMA ALDELYA, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Android app is one way that is effective, efficient, and innovative media promotion. The rapid development of technology makes android be an option for the delivery of information easily by the target audience. Currently West Sumatra already widely known by tourists, but there are still a lot of tourists in finding a tourist site. That requires a media that provides location information of tourism in West Sumatra. This android app includes a way that could mempromsikan effective manner and efficiency. The purpose of this Minangkabau Raun Android design is easier for tourists to find the location of tourism in West Sumatra. Making it easier for travelers looking for any tourist destinations in West Sumatra.Methodology The approach used is the SWOT analysis to understand all the information on an issue. The analysis in the form of strategic planning is used to evaluate the strengths, weaknesses, opportunities and threats in the design process. So the selection of more effective android application media and the message to be conveyed easily understood by the target audience.Applications Raun Minangkabau at the start with a choice of 5 main area of tourism in West Sumatra, then after selecting one of the city / county sites will appear several choices of tourist attractions in the city / county and, when the tourist attractions that we want we choose will appear gallery, tourist information and maps that function navigator directs the audience straight to the desired sites. In addition to Android applications, these media include media support such as watches, Tumbler, T-Shirt, Drawstring Bag, pillow, sticker, x-banner, poster which aims to strengthen the promotion of major media.Keyword: Android Apps, Raun Minangkabau, of tourism.